Pat O'Toole - Ladder Livestock Company, Wyoming - O'Toole, Pat, speaker (Colorado State University. Libraries, 2011)
In Panel discussion #2, Four ranchers with varying levels of experience with ecosystem markets describe how and why they became involved in ecosystem markets. Moderated by Terry Fankhauser from Colorado Cattlemen's Association.

In this video is Pat O'Toole, a rancher from Ladder Livestock Company in Wyoming.
Rancher panel - experiences from participating in ecosystem service initiatives
Presented at a workshop entitled "Stepping toward the future: marketing environmental services on working lands of the American West" on May 23-25, 2011 on the CSU campus. The purpose of the workshop was to bring together regional and national leaders from the ranching community, conservation organizations, businesses, universities, and government to explore ways to catalyze the development of payments for ecosystem services in Colorado and across the American West. Over 80 participants attended the conference, which also highlighted the CCC's work to create an ecosystem marketplace in northern Colorado.
Includes recorded video presentation.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: grasslands; ecosystem services; environmental markets; grazing